The Pre-Transplant Non-HLA Antibody Burden Associates With the Development of Histology of Antibody-Mediated Rejection After Kidney Transplantation - Senev, Aleksandar; Ray, Bryan; Lerut, Evelyne; Hariharan, Jayasree; Heylen, Christine; Kuypers, Dirk; Sprangers, Ben; Emonds, Marie-Paule; Naesens, Maarten (Frontiers in Immunology, 2022)
Background: Many kidney allografts fail due to the occurrence of antibody-mediated rejection (ABMR), related to donor-specific anti-HLA antibodies (HLA-DSA). However, the histology of ABMR can also be observed in patients without HLA-DSA. While some non-HLA antibodies have been related to the histology of ABMR, it is not well known to what extent they contribute to kidney allograft injury. Here we aimed to investigate the role of 82 different non-HLA antibodies in the occurrence of histology of ABMR after kidney transplantation. Methods: We included all patients who underwent kidney transplantation between 2004-2013 in a single center and had biobanked serum. Pre- and post-transplant sera (n=2870) were retrospectively tested for the presence of 82 different non-HLA antibodies using a prototype bead assay on Luminex (Immucor, Inc). A ratio was calculated between the measured MFI value and the cut-off MFI defined by the vendor for each non-HLA target. Results: 874 patients had available pretransplant sera and were included in this analysis. Of them, 133 (15.2%) received a repeat kidney allograft, and 100 (11.4%) had pretransplant HLA-DSA. In total, 204 (23.3%) patients developed histology of ABMR after kidney transplantation. In 79 patients (38.7%) the histology of ABMR was explained by pretransplant or de novo HLA-DSA. The multivariable Cox analysis revealed that only the broadly non-HLA sensitized (number of positive non-HLA antibodies) patients and those with the highest total strength of the non-HLA antibodies (total ratios of the positive non-HLA antibodies) were independently associated with increased rates of histology of ABMR after transplantation. Additionally, independent associations were found for antibodies against TUBB (HR=2.40; 95% CI 1.37 – 4.21, p=0.002), Collagen III (HR=1.67; 95% CI 1.08 – 2.58, p=0.02), VCL (HR=2.04; 95% CI 1.12 – 3.71, p=0.02) and STAT6 (HR=1.47; 95% CI 1.01 – 2.15, p=0.04). Conclusions: This study shows that patients highly and broadly sensitized against non-HLA targets are associated with an increased risk of ABMR histology after kidney transplantations in the absence of HLA-DSA. Also, some pretransplant non‐HLA autoantibodies are individually associated with increased rates of ABMR histology. However, whether these associations are clinically relevant and represent causality, warrants further studies.